Peran Motivasi Kerja dalam Memoderasi Pengaruh Kepuasan Kerja Karyawan dan Komitmen Organisasi terhadap Kinerja Karyawan PT. PLN (Persero) - Hartiwi Prabowo; Vana Lestari (Bina Nusantara University, 2013)
Employee performance is a major factor determining organizational success. Various complaints that arise related to power outages and high electricity tariff increase people demand as consumers on excellent service. Total consumers of PLN Disjaya reach 3,759,546 subscribers (March 2011), it is one unit that has the largest number of subscribers compared to other PLN units, and also provides the largest contribution to revenue. On a survey of Integrity, PLN Disjaya service from 2006 to 2010 showed that over the last five years, PLN Disjaya integrity is below target. The purpose of this study is to analyze the role of motivation in moderating influence between job satisfaction and organizational commitment partially and simultaneously on employee performance. Data collection techniques used questionnaires to 160 employees as respondents; data analysis techniques used Regresion Moderated Analysis (MRA). The results showed the role of motivation can moderate the job satisfaction on employee performance, but by individual motivation cannot moderate the commitment to employee performance.